Delayed Diagnosis of Nasal Natural Killer/T-Cell Lymphoma. (15th December 2013) - Villwock, Jennifer A.; Jones, Kristin; Back, Jason; Goyal, Parul
Abstract : Midline destructive lesions of the face have multiple possible etiologies. The majority of these cases are found to be due to an extranodal lymphoma of natural killer/T-cell-type non-Hodgkins lymphoma (NKTL). Unfortunately, diagnosis is often delayed. With variable presenting complaints, including nonspecific issues like chronic rhinosinusitis or nasal congestion, initial treatments are aimed at these presumed diagnoses. Only as the lesion progresses do overt signs of destruction occur. As with our patient, who was initially treated for presumed infection and abscess, final diagnosis often does not occur until several months, and several antibiotic courses, from initial presentation. As such, it is important for this rare entity to remain in the clinician's differential diagnosis for nasal lesion.